Peninjauan Kembali Kebutuhan Dimensi Saluran Drainase Sekunder di Kelurahan Balaroa Kecamatan Palu Barat (REKONSTRUKSI TADULAKO: Civil Engineering Journal on Research and Development, 2026)
Drainage conditions in Palu City still need attention, especially in the drainage in Balaroa Village, drainage dimensions that do not match the required dimensions can cause flooding problems because the channel cannot accommodate the design flood discharge. One of them occurred in the Secondary Drainage in Balaroa Village, West Palu Subdistrict, the narrowing of the drainage channel along 200 meters resulted in disruption of the function of the drainage. The purpose of this writing is to determine the performance and the need for appropriate dimensions in the Secondary drainage Balaroa West Palu District. The research process begins with the collection of secondary data in the form of rainfall data, population data and also primary data obtained through direct measurements in the field. Then the abnormality test is carried out, analyzing the frequency of rainfall using the log person type III method, calculating discharge discharge, design flood discharge, evaluating drainage capacity and calculating channel dimension requirements. The results showed that the results of the evaluation of drainage performance along the 560 meters, at STA 0+000 to STA 0+200 were not able to accommodate the design discharge where the results of the design flood discharge with a 10-year return period of 14,935 m3/s were obtained, with the existing channel capacity at STA 0+000 of 3,390 m3/s, then the calculation of channel dimension requirements with an average channel discharge of 22,450 m3/s was carried out so that in the future a channel with a capacity corresponding to the design flood discharge could be built